Eugénie et Mathilde, ou, Mémoires de la famille du comte de revel - Souza-Botelho, Adélaïde-Marie-Emilie Filleul, marquise de, 1761-1836 (MHRA critical texts, 2014)
Madame de Souza was an eighteenth-century political journalist of undisputed talent. She did not fear to accuse religion of falsely justifying intolerant political attitudes, or using indoctrination for little human gain. She dared to show that this achieved immediate social dislocation, and, in the long-term, grief and financial dysfunction. Eugénie et Mathilde, which documents revolutionary decisions made in Emigration, and the irrevocable futility of losing family, home, rank and property in war, fully reflects her approach. It is a complex and compelling story of one family and its experience of 1789-1797 - the years of exile during the French Revolution. Heart-rending decisions, forced departures, capital punishment and death of loved-ones make the novel as topical now as it was on the eve of Napoleon's Russian Campaign. Souza's plea for tolerance, fraternity and compromise on the part of the State and its enemies has a relevance that stretches out to the 21st Century; her message from her to include women in politics and not to make them suffer the unnecessary death of fathers, husbands, children and friends is even more current. This edition lifts the veil on a literary form of anti-sentimental romance, or the art of making historically accurate accounts masquerade as fiction. That, more than anything else, was Madame de Souza's forte of her.